Studies in the theory and method of New Testament textual criticism - Epp, Eldon Jay; Fee, Gordon Donald, 1934- (Grand Rapids, MI Eerdmans, 1993)
Includes bibliographcial references and indexes.
Keywords: Bible. N.T. -- criticism, textual